PERAN BANK JATIM DALAM IMPLEMENTASI QRIS DAN PENGELOLAAN RISIKO OPERASIONAL PADA PEDAGANG PASAR TRADISIONAL - Ida Ayu Nuh Kartini; Riyana Astutik Ningsih; Aulia Sintya Azzahra; Waasi’u Khairunnisa; Aulya Nurul Islamiyah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The development of digital payment systems encourages the need for assistance for traditional market traders to adapt to the use of QRIS in a secure and effective manner. This community service activity was carried out with traditional market traders in collaboration with Bank Jatim, aiming to improve traders’ understanding of QRIS usage and operational risk management in non-cash transactions. The implementation methods included field observations, interviews with Bank Jatim officers, as well as direct socialization and education for traders regarding transaction procedures and potential operational risk. The results indicate an improvement in traders’ understanding of QRIS, particularly in terms of transaction security and error prevention. In addition, traders became more confident in accepting digital payments, which supports smoother transactions and encourages financial inclusion in traditional markets.